1981
DOI: 10.1111/j.1471-4159.1981.tb06305.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunofluorescence and Histochemical Methods for Neural M1 Pyruvate Kinase Localization

Abstract: The distribution of pyruvate kinase (ATP pyruvate phosphotransferase, EC 2.7.1.40) in the nervous system has been studied by both immunofluorescence and a histochemical procedure using nitro blue tetrazolium. The localization in various parts of rat central nervous system in situ, cerebellar and cerebral cortex, was compared to that found in vitro in cultures of cerebellum, spinal ganglia, cerebral astrocytes, and skin fibroblasts. (1) Pyruvate kinase was found predominantly in the cytoplasm of neuronal cell b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Although it has been demonstrated that the expression of transporters and enzymes involved in the hypothesis of this review are similar to that observed in situ (Castro et al. 2007, 2008; Gali et al. 1981; Loaiza et al.…”
Section: The Ascorbic Acid Metabolic Switchmentioning
confidence: 51%
See 1 more Smart Citation
“…Although it has been demonstrated that the expression of transporters and enzymes involved in the hypothesis of this review are similar to that observed in situ (Castro et al. 2007, 2008; Gali et al. 1981; Loaiza et al.…”
Section: The Ascorbic Acid Metabolic Switchmentioning
confidence: 51%
“…These differences might be of importance for regulation of brain glycolysis in the different cellular compartments of the brain. PK is expressed in neurons and astrocytes (Gali et al. 1981).…”
Section: Glucose Use and Glucose Transporters In Brainmentioning
confidence: 99%
“…The pyruvate kinase isoenzyme M1 (KPYM) was downregulated in trans-differentiated cells but its presence is considered important for nerve endings [30]. Likewise the down regulation of neurotrophic factor-3 (NT-3) in neuronal cells is noteworthy since this factor is necessary for the development of mature neurons and enteric nervous system but it is not essential for the generation of newly differentiated neural cells [31].…”
Section: Resultsmentioning
confidence: 99%